Progressive Training Program Improves Aerobic Capacity and Physical Fitness in Student Soccer Athletes - Rahima Rahima; Hardhono Susanto; Rostika Flora; Udin Bahrudin; Sukendro Sukendro (Eduvest - Journal of Universal Studies, 2025)
The endurance of soccer players in Indonesia is generally still low. Aerobic capacity is an important component for improving physical fitness and endurance. When comparing several age groups, young players have less physical fitness. This study aimed to determine the effects of progressive training on changes in the maximum oxygen volume (VO2max) and heart rate (HR) based on recovery time. This study is quasi-experimental with a control group design and was conducted on student soccer athletes. Sixty athlete students who met the inclusion criteria were divided into a control group (n=30) and a progressive training group (n=30). The intervention consisted of progressive training for ten weeks with marathon running at distances of 150, 200, and 300 meters with rest intervals for each distance. The training load was gradually increased by increasing the number of repetitions every week. VO2 max, and Heart Rate were evaluated before and after the program. The results shown that the VO2 max was significantly different between the groups (p<0.001), and the Heart Rate of the subjects in both groups decreased from start to finish. Notably, the HR in the progressive training group was lower than the control group. In conclusion, progressive training is effective in improving aerobic capacity and physical fitness.